RELIGION AND AI: ETHICAL RISKS OF AIFICATION OF DIGITAL HUMAN - Oleg Pavenkov (PEOPLE: International Journal of Social Sciences, 2026)
The development of artificial intelligence is significantly impacting religious and moral values, and this dynamic is fundamentally changing our perception of Christianity. With the increasing virtualization and the introduction of AI into human lives, human consciousness, including religious and moral ones, is also changing. One possible scenario, which raises concerns, is the increasing impact of AI system not only on democratic political structuresi but also on transformation of humans into co-operators of AI technologies and digital humans. This process can be called as AIfication of human nature and human mind. Aification scenario appears realistic especially in the sphere of modern education where implementation AI technologies has changed traditional educational processes by facilitating adaptive, personalized, and data-informed learning practices. Discussion concerning the transformation of religious and moral thinking under the influence of AI is going on. Today, AI is embedded in the technologies through which we obtain information and interact with the world and each other, such as social media. While these platforms are known to exert pressure on collective thinking and aggressive attitudes toward dissenters, it is the automation of such processes by AI that is unique. This aspect is still being studied, but it already raises serious questions. For example, can AI moderate social media, taking into account the plurality of based on value orientations opinions, rather than simply blocking dissenting views? Or can AI act as an HR manager, judge, or police officer, whose decisions influence the fate of people? The global question is: can a mindless technology without life and consciousness determine the fate of a living person? Although the solutions to these questions are beyond our control, it is important to raise them and emphasize the need for moral responsibility in this process. There is also another danger of technological progress and the development of AI—a tendency toward hubris and forgetfulness about the spiritual source of human existence. Nietzsche was right in diagnosing an era when society lives as if God does not exist and places its hopes on AIiii. From healing diseases and predicting disasters to driving cars, human beings increasingly trust AI-technologies. Such unconditional and unreasonable faith in the power of AI and its objectivity can lead to catastrophic moral consequences and creation of new religion of AI. Current shifts in ethical views, especially in certain regions, may create the illusion of a correct path. However, with the expansion of global connections fuelled by technology, it is necessary to listen to the quiet voices of the past traditions, when both Christianity, Islam and other religions served as the real foundations of worldview for majority of population. Current ethical discussions of AI and the range of technologies being applied clearly demonstrate that technological progress will not replace moral and spiritual progress of personality. On the contrary, without moral strengthening and bases on traditional moral systems AI progress could accelerate moral degradation on an exponential scale. AIfication of a person can be understood as the process by which AI system’s attributes and way of behaviors are increasingly replicated, simulated, or augmented by humans. Digitial human not only perform tasks associated with AI system but also mimic or enhance AI-like way of ’understanding’ and ‘interaction’. From person logical point of view AIficaion is the process of development of Artificial You and Artificial Self in internal worlsiv. This global process of AIfication is reinforced by the ubiquitous promotion of AI technologies, creating the illusion of progress while ignoring the aspect of moral and intellectual degradation. We often perceive the human mind as akin to a computer, perhaps even an imperfect one, requiring the assistance of machines. In fact, humanity can exist without AI. However, in the face of imposed artificial needs, such as mobile devices and the internet, it is increasingly difficult for humans to cope without AI systems, which, if abused, can turn into machines of oppression. The danger of the immoral use of AI is real and should not be ignored. However than demonizing technology, both Christians and representatives of other religions are encouraged to "teach" AI patterns of such moral values as love, mercy, and compassion.